Computer accounting with Sage 50 complete accounting 2013 - Carol Yacht (McGraw-Hill, 2014)
Part 1: Exploring SCA (Sage Complete Accounting) 2013 Chapter 1: Introduction to Bellwether Garden Supply Chapter 2: Vendors Chapter 3: Customers Chapter 4: Employees Chapter 5: General Ledger, Inventory, and Internal Control Chapter 6: Job Cost Chapter 7: Financial Statements Chapter 8: Stone Arbor Landscaping: Time & Billing Part 2: SCA 2013 for Service Businesses Chapter 9: New Company Setup and Beginning Balances Chapter 10: Maintaining Accounting Records for Services Businesses Chapter 11: Completing Quarterly Activities & Closing the Fiscal Year Project 1: Sherry Pierce, Accounting Project 1A: Student-Designed Service Business Part 3: SCA 2013 for Merchandising Businesses Chapter 12: Vendors & Purchases Chapter 13: Customers & Sales Chapter 14: Inventory & Services Chapter 15: Employees, Payroll, and Account Reconciliation Project 2: Mountain Sports Project 2A: Student-Designed Merchandising Business Part 4: Advanced SCA 2013 Applications Chapter 16: Customizing Forms Chapter 17: Import/Export Chapter 18: Microsoft Word and Templates Project 3: Springfield Computer Club Project 4: CW Manufacturing, Inc. Project 4A: Student-Designed Project Appendix A: Troubleshooting Appendix B: Accounting Information Systems Appendix C: Accounting Principles Review Appendix D: Glossary Index